Outcomes of head and neck cancer management from two cancer centres in Southern and Northern Europe during the first wave of COVID-19. Issue 3 (June 2022) - Tagliabue, Marta; Russell, Beth; Moss, Charlotte; De Berardinis, Rita; Chu, Francesco; Jeannon, Jean-Pierre; Pietrobon, Giacomo; Haire, Anna; Grosso, Enrica; Wylie, Harriet; Zorzi, Stefano; Proh, Michele; et al.
Objective: To describe the approach and outcomes from two cancer centres in Southern and Northern Europe during the first wave of coronavirus disease 2019 (COVID-19) of patients with head and neck cancer (HNC). Methods: Data collection was performed on a retrospective cohort of patients surgically treated for primary HNC between March and May 2020, using data from two tertiary hospitals: the European Institute of Oncology (Milan) and Guy's & St Thomas' NHS Foundation Trust (London). Results: We included 77 patients with HNC. More patients with COVID-19 were taking angiotensin-converting enzyme (ACE) inhibitors and had Clavien-Dindo Classification grade I compared to negative patients, respectively (60% vs 22% [ p = 0.058] and 40% vs 8% [ p = 0.025]). Multivariate logistic regression analyses confirmed our data ( p = 0.05 and 0.03, respectively). Sex and age were statistically significantly different ( p = 0.05 and <0.001 respectively), showing more male patients (75% vs 53.66%, respectively) and more elderly patients in Italy than in the United Kingdom (patients aged >63 years: 69.44% vs 29.27%). Conclusions: This study presents a large cohort of patients with HNC with nasopharyngeal swab during the first peak of the COVID-19 pandemic in Europe. Patients with HNC with COVID-19 appeared more likely to develop postsurgical complications and to be taking ACE inhibitors. The preventive measures adopted guaranteed the continuation of therapeutic surgical intervention.